The Implementation of Animated Videos on the Independence of Children Aged 5-6 Years - Dessi Andriani; Maryani Maryani (Universitas Sebelas Maret, 2026)
Early childhood independence is crucial for holistic development, and animated videos have the potential to motivate it through visual stimulation. This study aims to examine the implementation of animated videos in enhancing the independence of children aged 5 to 6 years. Independence is a vital aspect of child development that encompasses the ability to perform daily tasks without depending on others. The research method employed is descriptive qualitative, with data collection conducted through observation, interviews, and documentation. Data analysis techniques were carried out using data source triangulation, data reduction, data display, and conclusion drawing, in accordance with the Miles and Huberman model. The research subjects consisted of six children and one teacher. The results indicate that after watching animated videos, children began to demonstrate an increase in independence, such as completing assigned tasks, having the courage to separate from parents, and preparing themselves for learning. Engaging and interactive animated videos successfully motivated the children to imitate the independent behaviors presented. Furthermore, the role of teachers and the school environment is essential in supporting the development of children's independence. This study contributes to the understanding of the effectiveness of learning media in early childhood education and is expected to serve as a reference for educators and parents in developing children's independence.